Use of blood lactate accumulation to validate a method of interval workout design - Springer, B. A.; Lally, D. A. (Medicine & Science in Sports & Exercise, 1996)
The responses of 13 male runners to different types of workouts were evaluated. The following were found: 1. Blood lactate levels do not indicate workout intensity or demands when the repetition distance is short and the rest interval is long or when the volume of work and repetition distance are very long. 2. Blood lactate levels and training heart rates do not differentiate workout intensities if the speeds used in repetitions are those to which the athlete has become accustomed. 3. Heart rate recovery did not diminish over the course of either short-duration or long-duration workouts. Implication. Blood lactate levels, heart rates, and recovery heart rates do not differentiate between workouts when the content is familiar (adapted) and of similar total demand. These three indices have very limited value for assessing the workout responses of well-trained serious athletes.